Studi Pustaka Taman Air Kerajaan di Kabupaten Karangasem - NANIEK KOHDRATA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2012)
ABSTRACT Literature Study of Royal Water Gardens at Karangasem Regency Human beings depend on water for their everyday life. Every culture around the world acknowledges water in various aspect of life. Despite the use of water in human daily life, lots of human events and activities use water for religion, recreation, aesthetic, and social function. This study portrays the use of water as royal garden theme. It examines the water functions in two royal gardens in Karangasem Regency, in Bali, which are Taman Sukasada (Sukasada Garden) and Taman Tirta Gangga (Tirta Gangga Garden). Those two gardens show that water can be manipulated for design purposes. The royal gardens in Karangasem signify the water elements as design inspiration, which turn out to the gardens’ multi-functions. Keywords: water garden, sukasada garden, tirta gangga.